2005
DOI: 10.1007/s10194-005-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the “carry–over effect” following successful termination of chronic migraine in the adolescent with short–term dihydroergotamine, dexamethasone and hydroxyzine: a pilot study

Abstract: IntroductionDaily oral preventive therapies for frequent and/or disabling migraine attacks are fraught with possible adverse effects and drug-drug interactions. Curative therapy is non-existent.Sensitisation of peripheral and central nociceptors are common mechanisms contributing to the development of chronic pain and, along with other morphological changes J Headache Pain (2005) 6:51-54 DOI 10.1007 Observations of the "carry-over effect" following successful termination of chronic migraine in the adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…11,12,[14][15][16][17][18] In 1986, Gallagher 20 published the first clinical trial with a control arm that supported the use of dexamethasone in the ED. In this trial of 130 patients, those receiving adjunctive dexamethasone therapy had a significantly lower rate of moderate or severe headache at 24 hours compared to the control group (28% vs. 71%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,[14][15][16][17][18] In 1986, Gallagher 20 published the first clinical trial with a control arm that supported the use of dexamethasone in the ED. In this trial of 130 patients, those receiving adjunctive dexamethasone therapy had a significantly lower rate of moderate or severe headache at 24 hours compared to the control group (28% vs. 71%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Uncontrolled clinical trials have shown that, in both the inpatient setting and the outpatient clinic setting, dexamethasone is highly effective in reducing the severity of migraine headache and the rate of headache recurrence. [11][12][13][14][15][16][17][18][19] Although initial controlled clinical trials demonstrated the same high-level of efficacy, [20][21][22][23][24][25][26] the results of several recent ED-based trials have questioned the utility of dexamethasone for this purpose. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] The goals of this systematic review were to critically appraise the existing literature and to provide recommendations for patient care regarding the use of dexamethasone for the prevention of headache relapse in patients with acute migraine headache in the ED.…”
mentioning
confidence: 99%
“…Chronic migraine remitted in seven adolescents given dihydroergotamine, dexamethasone and hydroxyzine parenterally once a week for three weeks. 97 We are unaware of evidence for the benefit of oral cyproheptadine, flunarizine, propanolol or riboflavin but these were considered effective in one clinic based study. 10 Riboflavin and Coenzyme Q10, singly or in combination, are worthy of trial because they are innocuous.…”
Section: Chronic Migrainementioning
confidence: 99%
“…Physiological effects of clowning were shown in a randomized control study reporting increased conception following in vitro fertilization procedures with clown-care [ 30 ]. The altered pain memory had a carry-over effect to other procedures similar to other pain treatments; effective pain medication alleviates pain in subsequent episodes [ 31 , 32 ]. However, if the procedure was experienced as traumatic, clowning could not alter this.…”
Section: Discussionmentioning
confidence: 99%